2023
DOI: 10.1111/imr.13228
|View full text |Cite
|
Sign up to set email alerts
|

Lipid mediators in the regulation of innate and adaptive immunity

Abstract: Life depends on lipids as the major structural components of membranes. Lipids are also crucial sources of energy in animals and humans. Fascinatingly, lipids have a diversity of additional roles in the immune system that range from acting as intercellular and intracellular signaling molecules to being modulators of membrane protein function, which influences tissue physiology in health and disease. How lipids are processed and metabolized has significant impact on cell and tissue function. In this issue of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Over the past two decades, numerous studies have shown that lyso-PS plays an important role in regulating a multitude of physiological processes in mammals, especially in the immune and central nervous systems. , Given this, the past few years have seen a significant increase in the number of reported mechanistic studies that causally relate lyso-PSs to diverse immunological phenotypes and their association with human diseases. , In this section, we will summarize the role and functions of lyso-PS in all the biological processes where significant mechanistic studies are available (Figure ), and we will conclude this section by highlighting some physiological processes where the roles of lyso-PS are as-of-yet poorly characterized.…”
Section: Biological Functions Of Lyso-psmentioning
confidence: 99%
“…Over the past two decades, numerous studies have shown that lyso-PS plays an important role in regulating a multitude of physiological processes in mammals, especially in the immune and central nervous systems. , Given this, the past few years have seen a significant increase in the number of reported mechanistic studies that causally relate lyso-PSs to diverse immunological phenotypes and their association with human diseases. , In this section, we will summarize the role and functions of lyso-PS in all the biological processes where significant mechanistic studies are available (Figure ), and we will conclude this section by highlighting some physiological processes where the roles of lyso-PS are as-of-yet poorly characterized.…”
Section: Biological Functions Of Lyso-psmentioning
confidence: 99%
“…As potent chemoattractants, LTs induce migration of neutrophils and macrophages during infection and tissue injury [315][316][317][318]. Up-to-date reviews about leukotrienes in immunity are available elsewhere [319,320]. LTs also contribute to tumorassociated inflammation, tumor growth and resistance to immunotherapy [321].…”
Section: Leukotrienes (Lts)mentioning
confidence: 99%